PENINGKATAN KUALITAS MINYAK GORENG KELAPA MELALUI VARIASI KONSENTRASI RAGI DAN LAMA PEMANASAN - Triani, Rini; Devinor, Monica; Izzata, Nasywa; Hervelly, Hervelly; Marthia, Nabila (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
Coconut oil is derived from coconut fruit. This study explores an alternative processing method involving yeast addition to shorten heating time. The yeast used is baker's yeast (Saccharomyces cerevisiae), which expedites emulsion breakdown in coconut milk. A factorial randomised block design was used with varying yeast concentrations (1%, 2%, 4%, 6%) and heating durations (30 and 45 minutes). Parameters tested included yield, moisture content, acid value, peroxide value, impurity level, turbidity, colorimetric value, and organoleptic properties of colour and aroma. A control group with 0% yeast was also evaluated. Analysis of variance indicated that yeast concentration significantly affects oil quality, whereas cooking time and their interaction do not. The best treatment, using 1% yeast concentration and a 30-minute cooking duration, produced the highest quality oil (de Garmo method), yielding 31.20% with superior characteristics (moisture content <1%, free fatty acid content at 0.33%, and a Brightness L* value of 44.68) compared to traditional commercial coconut oil. This method meets several elements of the Indonesian National Standard (SNI) and offers a more efficient production method yielding high-quality coconut cooking oil. Overall, yeast fermentation enhances coconut oil quality, surpassing the control group, and provides a more efficient production method for high-quality coconut oil.